Simulation of Thermodynamic Effect for Packaged Enclosures - Peng, Yan; Song, Kexin; Zhang, Tiancheng; Bao, Huaguang; Ding, Dazhi; Yang, Jian (Digest - IEEE Antennas and Propagation Society. International Symposium (1995), 2024)
LDMOS power tubes have a wide range of applications in electronic systems such as radar, communication base stations, wireless broadcasting towers, etc. However, with the increase in operating power, the requirements for heat dissipation and reliability of the packaged enclosure are also more severe. Therefore, in this paper, a thermodynamic coupling method is proposed to analyze the multilayer ceramic housings with the finite difference time domain method. By setting the temperature load, fixed displacement and other boundary conditions, the deformation distribution of the encapsulated shell can be obtained. Thus, the accuracy and the efficiency of the proposed algorithm are verified by comparing the numerical simulation with the commercial software.